The Obstacles of Inclusive Education Implementation in Indonesia: A Systematic Review - Komarudin, Komarudin; Kaeni, Nor Faizah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
The study is to investigate the obstacles to inclusive education implementation in Indonesia. The method employed in the study was a systematic review, namely a systematic search performed by the researcher using five electronic databases; Wiley, Pumbed, ScienceDirect, Ebsco, and Google Scholar. There was a year limitation in the article publication period, namely articles published in the last ten years (2012 – 2022). The data were analyzed using thematic analysis aiming at identifying study patterns. Based on the data analysis result, there are nine factors inhibiting inclusive education in Indonesia, namely poor management of inclusive schools, incompatible curriculum for students, low regular teachers’ competence in handling special needs students, inadequate quantity and quality of Special Advisors Teachers working at inclusive schools, unidentified variety of special needs students along with problems complexities, inadequate operational financing of inclusive education, inadequate standardized supporting facilities and infrastructure of inclusive education implementation, less leading roles and cooperation between schools and parents, and lack of cooperation between schools and external stakeholders.